2012
DOI: 10.7771/1541-5015.1348
|View full text |Cite
|
Sign up to set email alerts
|

Examining How Middle School Science Teachers Implement a Multimedia-enriched Problem-based Learning Environment

Abstract: This study examined how a group of ten middle school teachers implemented a technology enriched problem-based learning (PBL) environment. The goal was to understand their motivation, document their implementation techniques, and identify factors that teachers considered important in using technology-based PBL tools in their teaching.The analysis identified four factors that provided the impetus for teachers to consider the adoption of technology-based PBL instruction. These factors are (1) the PBL program addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…In addition, a set of 10 multimedia-enriched cognitive tools (Kim & Reeves, 2007;Lajoie, 2000) are provided to scaffold student problemsolving processes. Research has shown scaffolds are needed to support students and teachers in implementing an open environment such as PBL (Ertmer & Simons, 2006;Kim & Hannafin, 2011;Liu et al, 2012).…”
Section: Attitude and Learning By At-risk Studentsmentioning
confidence: 99%
“…In addition, a set of 10 multimedia-enriched cognitive tools (Kim & Reeves, 2007;Lajoie, 2000) are provided to scaffold student problemsolving processes. Research has shown scaffolds are needed to support students and teachers in implementing an open environment such as PBL (Ertmer & Simons, 2006;Kim & Hannafin, 2011;Liu et al, 2012).…”
Section: Attitude and Learning By At-risk Studentsmentioning
confidence: 99%
“…The review showed, roughly, that out of these 36, five used K-12 student data as the major data source (i.e., Belland, Ertmer, & Simons, 2006;Brush, & Saye, 2008;Grant, 2011;Lehman, George, Buchanan, & Rush, 2006;Mergendoller, Maxwell, & Bellisimo, 2006), and four regarded technology as one of the core aspects of their observation (Belland et al, 2006;Brush, & Saye, 2008;Grant, 2011;Lehman et al, 2006). There were also 12 articles that used inservice or preservice teachers as the major data source (i.e., Asghar, Ellington, Rice, Johnson, & Prime, 2012;Goodnough, & Hung, 2008;Hakkarainen, 2011;Hjalmarson, & Diefes-Dux, 2008;Hmelo-Silver, Derry, Bitterman, & Hatrak, 2008;Liu, Wivagg, Geurtz, Lee, & Chang, 2012;Pecore, 2013;Tamim, & Grant, 2013;Walker et al, 2011;Weizman et al, 2008;Zhang, Lundeberg, McConnell, Koehler, & Eberhardt, 2010), and only four of these discussed technology explicitly Hakkarainen, 2011;Liu et al, 2012;Walker et al, 2011).…”
Section: Looking Backmentioning
confidence: 99%
“…Numerous research studies have been conducted on the eff ects of AR on middle school students' learning and motivation (e.g., Liu, Horton, Kang, Kimmons, & Lee, 2013;Liu, Horton, Olmanson, & Toprac, 2011), teachers' classroom implementation of the learning environment (e.g., Liu, Wivagg, Geurtz, Lee, & Chang, 2012), and the design and use of cognitive tools to support problem-solving (e.g., Liu, Yuen, Horton, Lee, Toprac, & Bogard, 2013). Th e focus of this paper, however, is to describe the approach we have developed to position AR as a sustained and continuous technology development and research project and to present our experiences as designers and developers of a PBL environment.…”
Section: Introductionmentioning
confidence: 99%